Productivity and profitability of shrimp mariculture in the Gulf of Nicoya, Costa Rica - Valverde-Moya, José A. (2014)
The main objective of this study was to evaluate productivity and economic profitability of commercial culture of marine shrimp in the Gulf of Nicoya, Costa Rica. The study was conducted in 2013 in commercial farms located in Abangaritos de Puntarenas, Colorado de Abangares, Puerto Jesús de Nicoya and Lepanto de Puntarenas. A total of 25.4 ha in 3 short cycles and 24.6 ha in one long cycle were used, following a conventional management plan. Productivity in kg/ha/year was higher in the 3 short cycles (2,605 kg/ha/year) compared to the long cycle (2,138 kg/ha/year). Variable costs of production for the short cycles were higher (US$8,389) than those for the long cycle (US$6,783), due to the implementation of 2 different culture technologies concerning stocking densities, harvests per year, product size, market price and water exchange. Income from farm sales was higher for the short cycles (US$14,671/ha) than for the long cycle (US$12,281/ha). The economic sensitivity analysis suggests the implementation of 3 short cycles rather than one long cycle based on higher productivity and profitability (US$5,536/ha compared to US$4,752/ha); however, the production strategy must be flexible to adjust to changes, particularly regarding product market price at any given moment.